Manejo agronómico del cultivo de naranjilla (Solanum quitoense Lam.) en el Ecuador. - VERA TORRES, MELVIN PAUL (2023)
The naranjilla or lulo (Solanum quitoense Lam.) is a species of great socioeconomic interest from the Solanaceae family, native to the Andes. The fruit is grown extensively in Peru, Ecuador, Colombia and Central America and is highly sought after in international agroindustrial product markets for its aroma, flavor and high content of nutritional ingredients. It plays an important role in the rural economy, as it is an important source of livelihood for some 12,000 families and provides employment and industrial development. In Ecuador, naranjilla is grown on some 10,000 hectares; this growth is due to increased domestic consumer demand and more dynamic prices. In this context, it should be noted that the lack of integrated pest management strategies and the limited number of recognized and effective varieties for producers and processors are the main reasons for the low productivity of this crop. In summary, this synthesis has evidenced the most significant points of the naranjilla crop and has determined that it contributes to the diversification of the Ecuadorian agroecosystem and represents a feasible option for national production.